2004
DOI: 10.1002/ccd.20124
|View full text |Cite
|
Sign up to set email alerts
|

Major noncardiac surgery following coronary stenting: When is it safe to operate?

Abstract: The optimal timing for elective noncardiac surgery (NCS) after coronary stenting is uncertain. We identified 47 patients who underwent elective NCS within 90 days of coronary stent placement between January 1995 and December 2000. Twenty-seven patients had NCS within 3 weeks of coronary stenting. Six of the seven in whom thienopyridine antiplatelet therapy was discontinued died postoperatively in a manner suggestive of stent thrombosis. In contrast, only 1 of the 20 patients in whom the thienopyridine was cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(124 citation statements)
references
References 33 publications
(22 reference statements)
1
111
0
12
Order By: Relevance
“…[10][11][12] From Mayo Clinic data, the cardiac risk was 3.8 to 7.1% during the first 6 weeks after stenting, but no event was seen in the patients who had surgery 6 to 8 weeks after stenting. 10) Schouten, et al reported that bare metal stent thrombosis occurred in 2.2% of patients who had noncardiac surgery 1 and 28 days after implantation; aspirin and clopidogrel had been withheld during surgery in patients with stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] From Mayo Clinic data, the cardiac risk was 3.8 to 7.1% during the first 6 weeks after stenting, but no event was seen in the patients who had surgery 6 to 8 weeks after stenting. 10) Schouten, et al reported that bare metal stent thrombosis occurred in 2.2% of patients who had noncardiac surgery 1 and 28 days after implantation; aspirin and clopidogrel had been withheld during surgery in patients with stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most available data about the risk of stent thrombosis in the perioperative period are derived from studies of bare metal stents. [10][11][12] Most authors and guidelines recommend that the surgery be avoided during the 12-month period of dual antiplatelet therapy after DES implantation, 13,14) however, there are limited data about the risk of perioperative thrombosis of DES. Therefore, we evaluated the incidence and the risk factors of DES thrombosis during the perioperative period.…”
mentioning
confidence: 99%
“…Several retrospective series have disclosed very high complication rates when surgery is performed early after PCI: the combined rate of MI and death is 10-38% within 4 weeks after BMS, but decreases to 3.8% and 2.8% when surgery is performed at 2 and 3 months respectively [14,15,16] (Figure 1). After DES, the rate of adverse cardiac events is more continuous (5.9% up to 12 months) and drops to 3.3% beyond 1 year, but the mortality is high (average 35%) [17].…”
Section: Antiplatelet Agents and Coronary Revascularisationmentioning
confidence: 99%
“…The early interruption of dual antiplatelet therapy to allow major non cardiac surgery during the first month after PCI with BMS leads to a cardiac mortality up to 86%, whereas it is 5% when the treatment is maintained perioperatively [14]. In an observational study (192 patients), the incidence of DES thrombosis after early non cardiac surgery (13% urologic operations) was 31% among patients who stopped clopidogrel before the required delay, but 0% among those who continued dual antiplatelet therapy [20]; all patients with stent thrombosis died.…”
Section: Antiplatelet Discontinuation In the Surgical Settingmentioning
confidence: 99%
“…al., 2002;Owens;Belkin et al, 2005;Pototski e Amenábar;et al, 2007). A interrupção pré-operatória de antiagregantes plaquetários, visando diminuir complicações hemorrágicas, pode desencadear um aumento rebote na ativação e agregação plaquetária, aumentando a probabilidade de um evento tromboembólico no paciente cardiopata (Sharma et al, 2004;Ferrari et al, 2005;Pfisterer et al, 2006;Krishman;Shenoy et al, 2008;Lillis et al, 2011;Park et al, 2012 (Floyd;Ferro, 2014), ou da inibição do receptor P2Y12 da adenosina difosfato (ADP), por meio do clopidogrel. As terapias mais utilizadas no tratamento e prevenção das DAC tem seu foco voltado para os ativadores ADP e TXA2 (Cheng, 2013).…”
Section: Introductionunclassified